(untitled) (Global Journal of Management and Business Research, 2025)
Abstract- Employee motivation is a key determinant of organizational productivity and success This paper explores how Human Resource Management HRM functions contribute to enhancing employee motivation particularly within public and private institutions in developing countries The study reviews relevant motivational theories and HRM strategies supported by a brief case analysis from a local institution in Somaliland The findings show that factors such as fair compensation training opportunities positive employee relations and clear career growth paths significantly influence employee performance and satisfaction